The Influence of Salary Satisfaction, Quality of Life, Job Satisfaction on Turnover Intention In Manufacturing - Pratama, Rachmatika; Dimas, Negoro Angga (Manajemen dan Bisnis, 2023)
This study aims to determine the cause of turnover intention in Manufacturing Industry companies in Tangerang, the results of which are expected to add information at the theoretical/scientific level of organizational management and also managerial implications for the company. Referring to the results of previous studies and empirical theories related to job satisfaction, Quality of Work, salary satisfaction, and turnover intention. This research was conducted using a survey method by distributing online questionnaires. Research respondents obtained up to 200 samples. The results of this study are that by using four Likert scales and using validity tests and hypothesis testing, they are valid with standard tests. This study provides significant support for the concept which states that salary satisfaction, job satisfaction, and quality of life affect turnover intention.